PHYSICAL QUALITY OF SOIL IN MECHANIZED THINNING OF Eucalyptus sp. - de Vargas, Francieli; Brandelero, Catize; Szymczak, Denise Andréia; Amaral, Lúcio de Paula; Petry, Mirta Teresinha; Werner, Valmir (Floresta, 2020)
The traffic of machines is the main cause of compaction of forest soils, causing soil deformations, due to the pressures exerted by the machines, both at the time of cutting and in the transshipment of wood. In this sense, this work had as objective to evaluate soil compaction, caused by the traffic of machines, in the mechanized thinning operation of Eucalyptus saligna Smith. This study was carried out in forest stands, in the municipality of Butiá, RS. Changes in soil physical properties were evaluated in three treatments: with no traffic; after cutting; and after wood transshipment. The forest inventory and collection of undisturbed soil samples were carried out to determine microporosity, macroporosity and bulk density. The experimental design was the completely randomized, in a bifactorial arrangement, with subdivided plots. For the comparison of the physical attributes, the Tukey test (p≤0.05) of significance was used. The results evidenced increase in soil density values, mainly in the treatment after transshipment<s> and decrease in macropores, with values close to and below the limit considerable as detrimental to the development of the plants. The knowledge of soil deformations caused by forest operations contributes to the improvement of future processes aiming to guide the physical quality of the soil, in order to offer beneficial conditions to the growth of the plants.</s>